Hotspots in the genomic architecture of field drought responses in wheat as breeding targets - Gálvez, Sergio; Mérida-García, Rosa; Camino, Carlos; Borrill, Philippa; Abrouk, Michael; Ramírez-González, Ricardo H; Biyiklioglu, Sezgi; Amil-Ruiz, Francisco; IWGSC; Dorado, Gabriel; Budak, Hikmet; Gonzalez-Dugo, Victoria; et al. (Functional & integrative genomics, 2019)
Wheat can adapt to most agricultural conditions across temperate regions. This success is the result of phenotypic plasticity conferred by a large and complex genome composed of three homoeologous genomes (A, B, and D). Although drought is a major cause of yield and quality loss in wheat, the adaptive mechanisms and gene networks underlying drought responses in the field remain largely unknown. Here, we addressed this by utilizing an interdisciplinary approach involving field water status phenotyping, sampling, and gene expression analyses. Overall, changes at the transcriptional level were reflected in plant spectral traits amenable to field-level physiological measurements, although changes in photosynthesis-related pathways were found likely to be under more complex post-transcriptional control. Examining homoeologous genes with a 1:1:1 relationship across the A, B, and D genomes (triads), we revealed a complex genomic architecture for drought responses under field conditions, involving gene homoeolog specialization, multiple gene clusters, gene families, miRNAs, and transcription factors coordinating these responses. Our results provide a new focus for genomics-assisted breeding of drought-tolerant wheat cultivars.
Keywords: Stress, Physiological; období sucha; genom rostlinný; šlechtění rostlin; lokus kvantitativního znaku; Triticum; Genome, Plant; Field drought tolerance; pšenice; Plant Breeding; fyziologický stres; Droughts; Plant spectral traits; Transcriptomics; Transcriptome; Quantitative Trait Loci; transkriptom